PREVENTION OF DENGUE HEMORRHAGIC FEVER THROUGH THE WASDEBANG (DENGUE HEMORRHAGIC FEVER ALERT) PROGRAM - Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Meli Diana; Khoiri Ahmad Fauzi Imron; Erfian Heris Ardianto; Zahid Fikri (Community Service Journal of Indonesia, 2021)
The WasDeBang (Dengue Hemorrhagic Fever Alert) program which was held in Kalipecabean Village, Candi District, Sidoarjo Regency is a form of community service to reduce the incidence of Dengue Fever which often increases when facing the rainy season. The activity will be held on September 5, 2021, at the house of a resident in Kalipecabean village, Candi District, Sidoarjo Regency. The target is the residents of the Kalipecabean village, Candi District, Sidoarjo Regency, in this case especially the PKK (Family Welfare Empowerment) women. Prior to the implementation of these activities, there is a process of preparing activities for approximately 3 weeks before the activities are carried out, starting from determining the theme of the extension to applying for permits to the relevant parties. As a form of evaluation, the activity was attended by 26 PKK mothers, the participants took part in the activity with great enthusiasm, health promotion activities could run on time and smoothly.